2002
DOI: 10.1046/j.1523-1755.2002.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between inducible nitric oxide synthase and heme oxygenase-1 in glomerulonephritis

Abstract: In anti-GBM nephritis iNOS up-regulates HO-1 presumably via high output NO production. Suprainduction of HO-1 attenuates iNOS activity. This negative feedback interaction points to HO-1 as a target for pharmacologic manipulation to reduce activity of prooxidant heme containing enzymes such as iNOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 10 publications
4
25
0
Order By: Relevance
“…In this sense, (Immenschuh et al 1999) have shown that HO-1 induction by LPS is mediated by NO. The attenuation of HO activity by NOS inhibitors has also been demonstrated both in vitro and in vivo models (Datta & Lianos 1999, Datta et al 2002. In our experiments, the increase in HO activity was preceded by the activation of the nitridergic system, and the blockade of this system by L-NAME significantly inhibited the LPS-dependent increase in HO activity.…”
Section: Discussionsupporting
confidence: 79%
“…In this sense, (Immenschuh et al 1999) have shown that HO-1 induction by LPS is mediated by NO. The attenuation of HO activity by NOS inhibitors has also been demonstrated both in vitro and in vivo models (Datta & Lianos 1999, Datta et al 2002. In our experiments, the increase in HO activity was preceded by the activation of the nitridergic system, and the blockade of this system by L-NAME significantly inhibited the LPS-dependent increase in HO activity.…”
Section: Discussionsupporting
confidence: 79%
“…In a number of in vitro and in vivo systems, there is a negative feedback interaction between iNOS and HO-1 and thus overexpression of HO-1 results in inhibition of iNOS expression or activity, which can be protective against NOmediated toxicity. 25,31,32 In this study, the HO-1 inhibitor SnPP partially inhibited iNOS expression and NO production in the rat adjuvant arthritis. It should be noted that although protoporphyrins are widely used as pharmacological tools to inhibit HO-1 activity, some of these agents can exert direct inhibitory effects on iNOS.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, therapeutic L-NIL administration significantly inhibited iNOS activity, as reflected by the reduction in NO 2 À þ NO 3 À levels, which was ineffective in controlling arthritis, in agreement with previous studies. 11 It has been found that iNOS activity upregulates HO-1 in inflammatory models such as rat nephritis 31 or mouse air pouch. 25 In the chronic phase of rat adjuvant arthritis, we have shown that selective iNOS inhibition results in decreased HO-1 expression, suggesting that endogenously NO generated by this enzyme participates Heme oxygenase-1 in adjuvant arthritis I Devesa et al in HO-1 induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be the main mechanism of regulation of NOS-2 by HO-1 in the zymosan- injected mouse air pouch, because we have previously reported that hemin administration does not affect NOS-2 protein expression in this model (Vicente et al, 2003). HO-1 could therefore be part of a general mechanism of defense against NO cytotoxicity, as suggested in studies using other animal models (Datta et al, 2002;Wei et al, 2003).…”
Section: Discussionmentioning
confidence: 67%